2011
DOI: 10.1007/s13355-011-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature between fractionated-dose irradiation doses on mating of the West Indian sweetpotato weevil, Euscepes postfasciatus (Coleoptera: Curculionidae)

Abstract: The effectiveness of the sterile insect technique (SIT) depends on the ability of released sterile males to mate with and inseminate wild females, but the use of gamma radiation to induce sterility negatively affects both somatic and reproductive cells of the sterilized insects. Recently, the effectiveness of fractionated-dose irradiation (FI), in which a sterilizing dose is delivered over time in a series of small irradiations, has been demonstrated in the West Indian sweetpotato weevil Euscepes postfasciatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the laboratory, irradiated weevils of E . postfasciatus are as active as normal weevils over the first 16 days after irradiation (Kumano et al , , ). Kinjo et al () estimated the survival of irradiated weevils at 90% or more in the field for 1 week and reported that 80% of the weevils may have survived for a further 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In the laboratory, irradiated weevils of E . postfasciatus are as active as normal weevils over the first 16 days after irradiation (Kumano et al , , ). Kinjo et al () estimated the survival of irradiated weevils at 90% or more in the field for 1 week and reported that 80% of the weevils may have survived for a further 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…3 cm diameter, 1 cm thickness) to prevent interference and casual mating. Newly collected weevils were designated a substantial age of 0-day-old [34]. We used sexually matured 12- to 17-day-old virgin weevils for subsequent behavioural studies.…”
Section: Methodsmentioning
confidence: 99%